# Solve: −(3x − 4) = −4(x + 1) − 2.

An equation is a mathematical statement with an 'equal to' symbol between two algebraic expressions that have equal values.

## Answer: Solving for x in the equation−(3x − 4) = −4(x + 1) − 2 we get x = -10

An equation is like a weighing balance with equal weights on both sides. If we add or subtract the same number from both sides of an equation, it still holds.

**Explanation:**

−(3x − 4) = −4(x + 1) − 2

let us expand the bracket and group the variables and constants.

- 3x + 4 = - 4x - 4 - 2

4x - 3x = - 6 -4

x = - 10